2018
DOI: 10.1021/acschembio.8b00446
|View full text |Cite
|
Sign up to set email alerts
|

The Base Pairing Partner Modulates Alkylguanine Alkyltransferase

Abstract: O-Alkylguanine DNA adducts are repaired by the suicide enzyme alkylguanine alkyltransferase (AGT). AGT facilitates repair by binding DNA in the minor groove, flipping out the damaged base, and transferring the O-alkyl group to a cysteine residue in the enzyme's active site. Despite there being significant knowledge concerning the mechanism of AGT repair, there is limited insight regarding how altered interactions of the adduct with its complementary base in the DNA duplex influence its recognition and repair. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…143 Several biochemical studies have revealed that sequence context, including the opposing base, impacts the repair of O 6 -MedG by AGT. 137,[144][145][146] In contrast, recent work from Essigmann and coworkers showed no specific mutational patterns arising from AGT repair in mouse cells treated with the alkylation agent N-methyl-N-nitrosourea (MNU). 147 However, there is little work on AGT accessibility to different chromatin states in mammalian cells.…”
Section: Methylating Agents (O 6 -Methylguanine)mentioning
confidence: 96%
“…143 Several biochemical studies have revealed that sequence context, including the opposing base, impacts the repair of O 6 -MedG by AGT. 137,[144][145][146] In contrast, recent work from Essigmann and coworkers showed no specific mutational patterns arising from AGT repair in mouse cells treated with the alkylation agent N-methyl-N-nitrosourea (MNU). 147 However, there is little work on AGT accessibility to different chromatin states in mammalian cells.…”
Section: Methylating Agents (O 6 -Methylguanine)mentioning
confidence: 96%
“…Adduct-directed nucleoside probes have also been exploited to probe the catalytic center of enzymes involved in repair and bypass of O 6 -alkylG adducts, e.g. TLS Pols or alkylguanine alkyltransferase . Translesion DNA synthesis continues DNA replication in the face of DNA damage, but the low fidelity of TLS Pols is responsible for many mutations observed in cancer .…”
Section: Synthetic Nucleosides As Probes To Investigate Translesion D...mentioning
confidence: 57%
“…TLS Pols or alkylguanine alkyltransferase. 28 Translesion DNA synthesis continues DNA replication in the face of DNA damage, but the low fidelity of TLS Pols is responsible for many mutations observed in cancer. 3 Therefore, elucidating the mechanisms of DNA adduct bypass by TLS Pols is crucial to understand DNA damage-induced mutagenesis.…”
Section: Investigate Translesion Dna Synthesismentioning
confidence: 99%